Un Gis per la conservazione e la valorizzazione della via Annia - Popilia - Ansioso, Francesca; Artese, Serena; Magarò, Floriana (GEOmedia, 2017)
This paper describes a methodology for implementing a GIS for the protection of artifacts, which also have historical-artistic significance, located along the route of Via Annia, better known as the ancient Roman road of Via Popilia. The aim of the work-group's research is to contribute to the development of a methodological process, with a view to the conservation and enhancement of Cultural Heritage. On a territorial scale, layer implementation will include information on geotechnical, hydro-geological, structural, urban and historical-artistic features. At the level of the single artifact, data entry is obtained through field work information gathering concerning historical and artistic relevance, location and structural aspects, and, furthermore, to develop a monitoring card, with an indication of the state of the art and critical points to be kept under control. Investigations are also to be carried out periodically with a view to necessary interventions for purposes of safety and structural recovery. Maintenance data will also be useful for future restoration and conservation projects. The pilot project concerns the case study of Ponte Sant'Angelo, known as the "Hannibal Bridge" (a Roman bridge from the 2nd century B.C.) and located between the municipalities of Altilia and Scigliano, in the province of Cosenza. The GIS can be used as an aid for the realization of tourism/related activities (guides, itineraries, on-site training, educational workshops, sites of special scientific interest, etc.).